Feedback Mechanisms for Cardiac-Specific MicroRNAs and cAMP Signaling in Electrical Remodeling. (August 2015) - Myers, Richard; Timofeyev, Valeriy; Li, Ning; Kim, Catherine; Ledford, Hannah A.; Sirish, Padmini; Lau, Victor; Zhang, Yinuo; Fayyaz, Kiran; Singapuri, Anil; Lopez, Javier E.; Knowlton, Anne A.; et al.
<x xml:space="preserve">Abstract</x> Background— Loss of transient outward K+ current (Ito) is well documented in cardiac hypertrophy and failure both in animal models and in humans. Electrical remodeling contributes to prolonged action potential duration and increased incidence of arrhythmias. Furthermore, there is a growing body of evidence linking microRNA (miR) dysregulation to the progression of both conditions. In this study, we examined the mechanistic basis underlying miR dysregulation in electrical remodeling and revealed a novel interaction with the adrenergic signaling pathway. Methods and Results— We first used a tissue-specific knockout model of Dicer1 in cardiomyocytes to reveal the overall regulatory effect of miRs on the ionic currents and action potentials. We then validated the inducible cAMP early repressor as a target of miR-1 and took advantage of a clinically relevant model of post myocardial infarction and miR delivery to probe the mechanistic basis of miR dysregulation in electrical remodeling. These experiments revealed the role of inducible cAMP early repressor as a repressor of miR-1 and Ito, leading to prolonged action potential duration post myocardial infarction. In addition, delivery of miR-1 and miR-133a suppressed inducible cAMP early repressor expression and prevented both electrical remodeling and hypertrophy. Conclusions— Taken together, our results illuminate the mechanistic links between miRs, adrenergic signaling, and electrical remodeling. They also serve as a proof-of-concept for the therapeutic potential of miR delivery post myocardial infarction.